Total deposition of sulphur to coniferous forests in Sweden - Taking canopy exchange into account - Pihl Karlsson, G.; Karlsson, P. E.; Hellsten, S.; Danielsson, H.; Kronnäs, V.; Akselsson, C. (Atmospheric Environment, 2024)
In the low deposition situation of today at many of the long-term Swedish forest monitoring sites, the deposition measured as precipitation to the open field, i.e. bulk deposition of oxidized sulphur (S) is often higher or equal to deposition of S sampled under the forest canopies, i.e. as throughfall. This suggests that the total S deposition estimated using throughfall is underestimated. The reason for this is direct exchange of S with the forest canopies, leading to an underestimation which becomes evident in low-deposition areas. We describe a new method to estimate the dry deposition of S to coniferous forest based on measurements with Teflon string samplers as surrogate surfaces, in combination with measurements of the net throughfall for sodium (throughfall subtracted with wet deposition). The wet deposition was estimated from bulk deposition measurements on the open field, corrected for dry deposition to the collectors. The method was applied for Norway spruce forests at monitoring sites across Sweden during nine years 2014–2022, and total deposition was calculated based on wet deposition and the estimated dry deposition. The estimated annual total deposition of S as a mean value for coniferous forests ranged between 0.8 and 5.2 kg S ha−1 yr−1 with lowest values in northern Sweden and highest in southwest Sweden. The share of dry deposition of the total S deposition was between 20 and 53%. The mean annual deposition of S measured as throughfall during 2014–2022 for three different regions in Sweden was between 16 and 41% lower compared to the corresponding total deposition estimated with the new method. The canopy exchange of S was analyzed on a monthly basis as the difference between the estimated total deposition and the measured throughfall deposition of S. At most sites, there was a canopy uptake of S during the summer months and a leakage of S during the winter months. This indicates that the canopy exchange of S is a phenomenon that involves some biological activity.